Phosphoric acid purification method and application thereof

The combined use of amino-modified multi-walled carbon nanotubes and sulfonic acid cationic resins solves the problems of low recovery and resin failure in phosphoric acid purification, realizes an efficient and environmentally friendly phosphoric acid purification process, and improves product purity and recovery rate.

CN120589704AActive Publication Date: 2025-09-05HUNAN YUNENG NEW ENERGY BATTERY MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511103921.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-07
Publication Date
2025-09-05
Estimated Expiration
2045-08-07

AI Technical Summary

Technical Problem

The existing phosphoric acid purification methods have low phosphoric acid recovery rates, resulting in reduced value of industrial phosphoric acid products. Traditional methods also have problems such as resin blockage or failure, high alkali solution consumption, and a large amount of waste residue.

Method used

Aminated multi-walled carbon nanotubes are used to adsorb dihydrogen phosphate ions in phosphoric acid under acidic conditions, and combined with sulfonic acid cationic resins to remove metal ion impurities. By adjusting the pH to 2-4, the resin performance degradation under strong acid conditions is avoided. Subsequent desorption forms a high-purity phosphoric acid solution, and ammonia water and aminated multi-walled carbon nanotubes are recycled.

Benefits of technology

The recovery rate of phosphoric acid is improved, the risk of resin contamination is reduced, resin blockage is avoided, alkali consumption is reduced, and the purification purity and product value are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The invention discloses a phosphoric acid purification method and application thereof, and belongs to the technical field of chemical raw materials. The method comprises the following steps: adjusting the pH value of a phosphoric acid crude product solution to 2-4, firstly adsorbing phosphoric acid anions by using aminated multi-walled carbon nanotubes, then removing metal ion impurities in the adsorbed solution by using sulfonic acid type cationic resin to obtain a purified solution, desorbing the aminated multi-walled carbon nanotubes by using ammonia water to obtain an ammonium phosphate solution, and drying the ammonium phosphate solution to obtain the phosphoric acid. Heating and decomposing to obtain a high-purity phosphoric acid solution, and collecting the high-purity phosphoric acid solution and a purified solution to obtain a purified product. According to the purification method, anions are removed firstly, phosphate precipitates of metal ions on the surface of the subsequent sulfonic acid type cationic resin are reduced, the pollution risk of the resin can be reduced, blockage or failure of the resin is avoided, and the purification purity is improved; loss of a large amount of phosphate precipitates is avoided in the treatment process, and the phosphoric acid recovery rate is high; wherein the ammonia water can be partially recycled, so that the consumption of alkali liquor can be reduced, and the cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of chemical raw materials, and in particular to a phosphoric acid purification method and application thereof. Background Art

[0002] Phosphoric acid, as a chemical raw material, is an important raw material in the organic synthesis industry. With the development of existing technologies, phosphoric acid can be produced into many downstream products through batching and refining, which are suitable for industries such as food, scientific research, electronics and medicine. Electronic chemicals have extremely high requirements for raw materials. Generally, industrial-grade raw materials have low purity, high impurity content and large fluctuations, which will lead to unstable impurity content in the final electronic-grade products and cannot meet the production needs of electronic chemicals. With the development of the industry, phosphoric acid is also used as one of the raw materials for iron phosphate in the lithium battery positive electrode material manufacturing industry. However, impurity elements in phosphoric acid interfere with the production process. Common elements such as Al, Ca, and Mg have a content of more than 2%, and further purification is required to obtain phosphoric acid that can be used in production.

[0003] Traditional purification methods include chemical precipitation, ion exchange, and crystallization. Chemical precipitation primarily involves adjusting the pH to form a precipitate to remove metallic impurities. The specific precipitation mechanism involves the combination of metal ions and phosphate ions under alkaline conditions to form a phosphate precipitate, which is then removed through sedimentation and filtration. While this method can remove metallic impurities, it also consumes a large amount of phosphoric acid, reducing the recovery rate and the product value of industrial phosphoric acid. It also consumes a large amount of alkali solution and produces a large amount of waste residue. Ion exchange removes impurity ions by exchanging cations, but high concentrations of anions can form precipitates or contaminate the resin surface with metal ions, leading to resin clogging or failure. This reduces the purity of the product, shortens the regeneration cycle and service life, and necessitates frequent regeneration. Summary of the Invention

[0004] The object of the present invention is to provide a phosphoric acid purification method and application thereof, so as to solve the problem of low phosphoric acid recovery rate in phosphoric acid purification in the prior art and improve the value of industrial phosphoric acid products.

[0005] The purpose of the present invention can be achieved through the following technical solutions: The present invention provides a method for purifying phosphoric acid, comprising the following steps: S1. Dissolve the crude phosphoric acid in water, adjust the pH to 2-4 with aqueous ammonia, add amino-modified multi-walled carbon nanotubes, ultrasonicate for 30-50 min, and allow to stand for adsorption for 8-12 h; S2, solid-liquid separation after adsorption, the separated solution is treated with sulfonic acid cationic resin to remove metal ion impurities to obtain a purified solution; S3 and the adsorbed amino-modified multi-walled carbon nanotubes are desorbed with ammonia water to obtain an ammonium phosphate solution, which is then heated and decomposed to obtain a high-purity phosphoric acid solution. The decomposed ammonia gas is absorbed by pure water to obtain ammonia water, which is then recycled. NH3 reacts with pure water to generate ammonia water (concentration 10-15%), which can be directly reused for S3 desorption, forming a closed-loop cycle.

[0006] S4. Collect the high-purity phosphoric acid solution and the purified liquid to obtain a purified product.

[0007] Phosphoric acid (H3PO4) is a polybasic acid that can ionize in aqueous solution to form the following main forms: H3PO4 (phosphoric acid molecule), H2PO4 - (dihydrogen phosphate ion), HPO4 2- (hydrogen phosphate ion), PO4 3- (Phosphate ion), when the pH is less than 2, it is mainly in the form of molecules; when the pH is 2-4, it is mainly in the form of dihydrogenphosphate ions; under alkaline conditions, it is mainly in the form of phosphate ions.

[0008] In the above steps, a small amount of alkaline ammonia water is first used to adjust the pH to 2-4. It is not necessary to increase the pH significantly. At this time, the phosphoric acid mainly exists in the form of dihydrogen phosphate ions. The amino multi-walled carbon nanotubes are used as the adsorbent. The amino multi-walled carbon nanotubes are introduced into the surface of the carbon nanotubes. Under acidic conditions, the amino groups will be protonated and react with H2PO4. - Adsorption is achieved through electrostatic interaction, desorption and regeneration are carried out under alkaline conditions, and it can be recycled.

[0009] Furthermore, the phosphoric acid content in the crude phosphoric acid product is ≥20wt%.

[0010] Furthermore, in S1, the concentration of the aqueous ammonia is 20-40 wt %. The use of high-concentration aqueous ammonia in S1 increases the pH value. Under conventional conditions, sulfonic acid cationic resins have limited acid resistance when used to remove metal ion impurities in phosphoric acid, and long-term use at a pH below 2 can lead to performance degradation.

[0011] Furthermore, the amino content of the amino-modified multi-walled carbon nanotubes is 0.4-0.6 wt % and the specific surface area is 200-260 m 2 / g.

[0012] Furthermore, the mass ratio of the amino-modified multi-walled carbon nanotubes to the crude phosphoric acid is 3-5:1.

[0013] Furthermore, the exchange capacity of the sulfonic acid cationic resin is ≥4.0 mmol / g.

[0014] Furthermore, in the purified liquid, Al<50ppm, Ca<200ppm, and Mg<2000ppm.

[0015] Furthermore, in S3, the concentration of the ammonia water is 10-28 wt %. The high pH causes the surface amino groups to be deprotonated, resulting in negative charges, which promotes the desorption of phosphate. - It will compete with phosphate for adsorption sites, further weakening the binding of phosphate to the adsorbent surface and accelerating desorption.

[0016] Furthermore, the temperature of the thermal decomposition is 180-220° C. Ammonium phosphate is slowly heated to 180-220° C., and the temperature is controlled to avoid dehydration of phosphoric acid to form pyrophosphoric acid, and decomposed into phosphoric acid and NH3, with a recovery rate of ≥95%, the reaction is controllable, and the process is feasible.

[0017] The present invention also provides an application of a phosphoric acid purification method, wherein the phosphoric acid raw material for lithium iron phosphate batteries is purified by the above purification method.

[0018] Beneficial effects of the present invention: (1) The present invention avoids the performance degradation problem of cation exchange resin under strong acid conditions by adjusting the pH value to 2-4. At this time, the phosphoric acid in the water mainly exists in the form of dihydrogen phosphate ions. The dihydrogen phosphate ions are first adsorbed by amino multi-walled carbon nanotubes. Compared with conventional anion exchange resins, the structure of amino multi-walled carbon nanotubes is more stable under strong acid conditions, and will not swell, break or fall off the functional groups. In addition, the adsorption capacity is large. The anions are removed first, and the subsequent phosphate precipitation of metal ions on the surface of the sulfonic acid type cationic resin is reduced, which can reduce the risk of resin contamination, avoid resin clogging or failure, and improve the purity of the purification.

[0019] (2) The present invention purifies phosphoric acid by adsorption on amino multi-walled carbon nanotubes and exchange with sulfonic acid type cationic resins. The ammonium phosphate formed after desorption of the amino multi-walled carbon nanotubes is decomposed to obtain a high-purity phosphoric acid solution. The sulfonic acid type cationic resin is exchanged to treat metal ion impurities in the solution. The purified liquid after treatment and the high-purity phosphoric acid solution are of high purity. There is no loss of a large amount of phosphate precipitation during the treatment process, and the phosphoric acid recovery rate is high.

[0020] (3) The amino multi-walled carbon nanotubes and sulfonic acid cationic resin used in the phosphoric acid purification process of the present invention can be recycled and reused, with low environmental pollution hazards. In addition, the ammonia water therein can be partially reused, which can reduce the consumption of alkali solution and reduce costs. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts shall fall within the scope of protection of the present invention.

[0022] Example 1 S1. Take the crude phosphoric acid and measure the phosphoric acid content by gravimetric method. The specific steps are as follows: 6.3 Determination of phosphoric acid content in "HG / T 4068-2022 Industrial Wet-process Crude Phosphoric Acid": Prepare the test solution: Weigh approximately 1g of crude phosphoric acid as the sample to the nearest 0.0002g. Place the sample in a 100mL beaker. Add 10mL of a 1+1 hydrochloric acid solution and a small amount of water. Cover with a watch glass and boil for 10 minutes. After cooling, transfer the solution to a 250mL volumetric flask, add 10mL of a 1+1 hydrochloric acid solution, and dilute to the mark with water. Shake well. Dry filter before use, discarding the first 20mL of the filtrate.

[0023] Prepare blank solution: Except for not adding sample, the amount of other reagents added is exactly the same as that of the test solution. This is the blank solution.

[0024] Simultaneously, treat the blank solution and the test solution in the same manner. Use a pipette to transfer 10 mL of the test solution and blank solution to each 250 mL beaker. Add water to a total volume of approximately 100 mL. Add 10 mL of nitric acid solution (1+1) and 35 mL of quinoline molybdate solution. Cover with a watch glass. Heat in a water bath until the contents reach 75°C for 30 seconds. (Do not use an open flame when heating, and do not stir during the addition of reagents or heating to prevent clot formation.) Cool to room temperature, stirring 3-4 times during the cooling process. Filter through a glass crucible that has been previously dried at 180°C to a constant mass. Filter the supernatant, and wash the precipitate six times by decantation, using approximately 20 mL of water each time. Transfer the precipitate to a glass crucible, wash four more times with water, and drain. Place the glass sand crucible together with quinoline phosphomolybdate in an electric drying oven at 180°C for 45 minutes, take it out, place it in a desiccator and cool it to room temperature, weigh it to an accuracy of 0.0002g, and after weighing, subtract the mass of the glass sand crucible to obtain the mass of the quinoline phosphomolybdate precipitate.

[0025] The phosphoric acid content is calculated as the mass fraction W1 of phosphorus pentoxide (P2O5), and the calculation formula is as follows: , Where: m1——the mass of quinoline phosphomolybdate precipitate generated in the test solution, in grams (g); m0——the mass of quinoline phosphomolybdate precipitate generated in the blank solution, in grams (g); m——the mass of the sample, in grams (g); 0.03207——The value of quinoline phosphomolybdate converted to phosphorus pentoxide.

[0026] The phosphoric acid content W1 of the crude phosphoric acid sample was calculated to be 21.30%.

[0027] The impurity element content was measured by inductively coupled plasma optical emission spectrometry, and the results are shown in Table 1: Table 1

[0028] After the test, 1 kg of crude phosphoric acid was dissolved in 2 L of pure water, and 25 wt% ammonia water was added to adjust the pH to 3. Aminated multi-walled carbon nanotubes were added and ultrasonically treated for 40 min, and then allowed to stand for adsorption for 10 h. The amino content of the aminated multi-walled carbon nanotubes was 0.45 wt%, and the specific surface area was 230 m 2 / g, and the mass ratio of amino-modified multi-walled carbon nanotubes to crude phosphoric acid was 3:1.

[0029] S2. After adsorption, the solid-liquid separation is performed. The separated solution is treated with a sulfonic acid cationic resin (type 001×7) to remove metal ion impurities to obtain a purified solution. The exchange capacity of the sulfonic acid cationic resin is 4.5 mmol / g, the exchange resin height is 2 mL, and the solution flow rate is 4 m / h.

[0030] The impurity element content in the purified solution was measured by inductively coupled plasma emission spectrometry. The results are shown in Table 2: Table 2

[0031] S3. The adsorbed amino multi-walled carbon nanotubes are desorbed using 15 wt% ammonia water to obtain an ammonium phosphate solution, which is slowly heated and decomposed at 200° C. for 40 min to obtain a high-purity phosphoric acid solution. The decomposed ammonia gas is absorbed by pure water to obtain ammonia water, which is recycled.

[0032] S4. Collect the high-purity phosphoric acid solution and the purified liquid, mix them to obtain a purified product, the mass of the purified product is m2 is 4450 g, and the phosphoric acid content W2 of the purified product is determined by weight method, W2 is 4.63%, and the impurity element content of the purified product is measured by inductively coupled plasma emission spectrometry. The impurity element content results are shown in Table 3: Table 3

[0033] The phosphoric acid recovery rate was calculated according to the formula: , Wherein, m2 is the mass of the purified product, g; m1 is the mass of the crude phosphoric acid used for purification, g; W1 is the phosphoric acid content of the crude phosphoric acid sample, %; and W2 is the phosphoric acid content of the purified product, %.

[0034] Substitute the above data into the formula for calculation. The specific calculation process is as follows: , The calculation results show that the phosphoric acid recovery rate P is 96.8%.

[0035] Example 2 The only difference from Example 1 is that different crude phosphoric acid is selected as the sample.

[0036] S1. Take the crude phosphoric acid and measure the phosphoric acid content by gravimetric method. The specific steps are as follows: 6.3 Determination of phosphoric acid content in "HG / T 4068-2022 Industrial Wet-process Crude Phosphoric Acid": Prepare the test solution: Weigh approximately 1g of crude phosphoric acid as the sample to the nearest 0.0002g. Place the sample in a 100mL beaker. Add 10mL of a 1+1 hydrochloric acid solution and a small amount of water. Cover with a watch glass and boil for 10 minutes. After cooling, transfer the solution to a 250mL volumetric flask, add 10mL of a 1+1 hydrochloric acid solution, and dilute to the mark with water. Shake well. Dry filter before use, discarding the first 20mL of the filtrate.

[0037] Prepare blank solution: Except for not adding sample, the amount of other reagents added is exactly the same as that of the test solution. This is the blank solution.

[0038] Simultaneously, treat the blank solution and the test solution in the same manner. Use a pipette to transfer 10 mL of the test solution and blank solution to each 250 mL beaker. Add water to a total volume of approximately 100 mL. Add 10 mL of nitric acid solution (1+1) and 35 mL of quinoline molybdate solution. Cover with a watch glass. Heat in a water bath until the contents reach 75°C for 30 seconds. (Do not use an open flame when heating, and do not stir during the addition of reagents or heating to prevent clot formation.) Cool to room temperature, stirring 3-4 times during the cooling process. Filter through a glass crucible that has been previously dried at 180°C to a constant mass. Filter the supernatant, and wash the precipitate six times by decantation, using approximately 20 mL of water each time. Transfer the precipitate to a glass crucible, wash four more times with water, and drain. Place the glass sand crucible together with quinoline phosphomolybdate in an electric drying oven at 180°C for 45 minutes, take it out, place it in a desiccator and cool it to room temperature, weigh it to an accuracy of 0.0002g, and after weighing, subtract the mass of the glass sand crucible to obtain the mass of the quinoline phosphomolybdate precipitate.

[0039] The phosphoric acid content is calculated as the mass fraction W1 of phosphorus pentoxide (P2O5), and the calculation formula is as follows: , Where: m1——the mass of quinoline phosphomolybdate precipitate generated in the test solution, in grams (g); m0——the mass of quinoline phosphomolybdate precipitate generated in the blank solution, in grams (g); m——the mass of the sample, in grams (g); 0.03207——The value of quinoline phosphomolybdate converted to phosphorus pentoxide.

[0040] The phosphoric acid content W1 of the crude phosphoric acid sample was calculated to be 37.41%.

[0041] The impurity element content was measured by inductively coupled plasma optical emission spectrometry, and the results are shown in Table 4: Table 4

[0042] After the test, 1 kg of crude phosphoric acid was dissolved in 2 L of pure water, and 25 wt% ammonia water was added to adjust the pH to 3. Aminated multi-walled carbon nanotubes were added and ultrasonically treated for 40 min, and then allowed to stand for adsorption for 10 h. The amino content of the aminated multi-walled carbon nanotubes was 0.45 wt%, and the specific surface area was 230 m 2 / g, and the mass ratio of amino-modified multi-walled carbon nanotubes to crude phosphoric acid was 3:1.

[0043] S2. After adsorption, the solid-liquid separation is carried out. The separated solution is treated with a sulfonic acid cationic resin (type 001×7) to remove metal ion impurities to obtain a purified solution. The exchange capacity of the sulfonic acid cationic resin is 4.5 mmol / g, the exchange resin height is 2 m, and the solution flow rate is 4 m / h.

[0044] The impurity element content in the purified solution was measured by inductively coupled plasma emission spectrometry. The results are shown in Table 5: Table 5

[0045] S3. The adsorbed amino multi-walled carbon nanotubes are desorbed using 15 wt% ammonia water to obtain an ammonium phosphate solution, which is slowly heated and decomposed at 200° C. for 40 min to obtain a high-purity phosphoric acid solution. The decomposed ammonia gas is absorbed by pure water to obtain ammonia water, which is recycled.

[0046] S4. Collect the high-purity phosphoric acid solution and the purified liquid, mix them to obtain a purified product, the mass of the purified product is m2 is 5233 g, and the phosphoric acid content W2 of the purified product is determined by weight method, W2 is 4.63%, and the impurity element content of the purified product is measured by inductively coupled plasma emission spectrometry. The impurity element content results are shown in Table 6: Table 6

[0047] The phosphoric acid recovery rate was calculated according to the formula: , Wherein, m2 is the mass of the purified product, g; m1 is the mass of the crude phosphoric acid used for purification, g; W1 is the phosphoric acid content of the crude phosphoric acid sample, %; and W2 is the phosphoric acid content of the purified product, %.

[0048] Substitute the above data into the formula for calculation. The specific calculation process is as follows: , The calculation results show that the phosphoric acid recovery rate P is 96.2%.

[0049] Example 3 The only difference from Example 1 is that different crude phosphoric acid is selected as the sample.

[0050] S1. Take the crude phosphoric acid and measure the phosphoric acid content by gravimetric method. The specific steps are as follows: 6.3 Determination of phosphoric acid content in "HG / T 4068-2022 Industrial Wet-process Crude Phosphoric Acid": Prepare the test solution: Weigh approximately 1g of crude phosphoric acid as the sample to the nearest 0.0002g. Place the sample in a 100mL beaker. Add 10mL of a 1+1 hydrochloric acid solution and a small amount of water. Cover with a watch glass and boil for 10 minutes. After cooling, transfer the solution to a 250mL volumetric flask, add 10mL of a 1+1 hydrochloric acid solution, and dilute to the mark with water. Shake well. Dry filter before use, discarding the first 20mL of the filtrate.

[0051] Prepare blank solution: Except for not adding sample, the amount of other reagents added is exactly the same as that of the test solution. This is the blank solution.

[0052] Simultaneously, treat the blank solution and the test solution in the same manner. Use a pipette to transfer 10 mL of the test solution and blank solution to each 250 mL beaker. Add water to a total volume of approximately 100 mL. Add 10 mL of nitric acid solution (1+1) and 35 mL of quinoline molybdate solution. Cover with a watch glass. Heat in a water bath until the contents reach 75°C for 30 seconds. (Do not use an open flame when heating, and do not stir during the addition of reagents or heating to prevent clot formation.) Cool to room temperature, stirring 3-4 times during the cooling process. Filter through a glass crucible that has been previously dried at 180°C to a constant mass. Filter the supernatant, and wash the precipitate six times by decantation, using approximately 20 mL of water each time. Transfer the precipitate to a glass crucible, wash four more times with water, and drain. Place the glass sand crucible together with quinoline phosphomolybdate in an electric drying oven at 180°C for 45 minutes, take it out, place it in a desiccator and cool it to room temperature, weigh it to an accuracy of 0.0002g, and after weighing, subtract the mass of the glass sand crucible to obtain the mass of the quinoline phosphomolybdate precipitate.

[0053] The phosphoric acid content is calculated as the mass fraction W1 of phosphorus pentoxide (P2O5), and the calculation formula is as follows: , Where: m1——the mass of quinoline phosphomolybdate precipitate generated in the test solution, in grams (g); m0——the mass of quinoline phosphomolybdate precipitate generated in the blank solution, in grams (g); m——the mass of the sample, in grams (g); 0.03207——The value of quinoline phosphomolybdate converted to phosphorus pentoxide.

[0054] The phosphoric acid content W1 of the crude phosphoric acid sample was calculated to be 48.92%.

[0055] The impurity element content was measured by inductively coupled plasma optical emission spectrometry, and the results are shown in Table 7: Table 7

[0056] After the test, 1 kg of crude phosphoric acid was dissolved in 2 L of pure water, and 25 wt% ammonia water was added to adjust the pH to 3. Aminated multi-walled carbon nanotubes were added and ultrasonically treated for 40 min, and then allowed to stand for adsorption for 10 h. The amino content of the aminated multi-walled carbon nanotubes was 0.45 wt%, and the specific surface area was 230 m 2 / g, and the mass ratio of amino-modified multi-walled carbon nanotubes to crude phosphoric acid was 3:1.

[0057] S2. After adsorption, the solid-liquid separation is carried out. The separated solution is treated with a sulfonic acid cationic resin (type 001×7) to remove metal ion impurities to obtain a purified solution. The exchange capacity of the sulfonic acid cationic resin is 4.5 mmol / g, the exchange resin height is 2 m, and the solution flow rate is 4 m / h.

[0058] The impurity element content in the purified solution was measured by inductively coupled plasma emission spectrometry. The results are shown in Table 8: Table 8

[0059] S3. The adsorbed amino multi-walled carbon nanotubes are desorbed using 15 wt% ammonia water to obtain an ammonium phosphate solution, which is slowly heated and decomposed at 200° C. for 40 min to obtain a high-purity phosphoric acid solution. The decomposed ammonia gas is absorbed by pure water to obtain ammonia water, which is recycled.

[0060] S4. Collect the high-purity phosphoric acid solution and the purified liquid, mix them to obtain a purified product, the mass of the purified product is m2 is 4074 g, and the phosphoric acid content W2 of the purified product is determined by weight method, W2 is 4.63%, and the impurity element content of the purified product is measured by inductively coupled plasma emission spectrometry. The impurity element content results are shown in Table 9: Table 9

[0061] The phosphoric acid recovery rate was calculated according to the formula: , Wherein, m2 is the mass of the purified product, g; m1 is the mass of the crude phosphoric acid used for purification, g; W1 is the phosphoric acid content of the crude phosphoric acid sample, %; and W2 is the phosphoric acid content of the purified product, %.

[0062] Substitute the above data into the formula for calculation. The specific calculation process is as follows: , The calculation results show that the phosphoric acid recovery rate P is 95.1%.

[0063] Example 4 The only difference from Example 1 is that aqueous ammonia is added to adjust the pH to 2.0 in S1.

[0064] S1. Take 1 kg of crude phosphoric acid same as that in Example 1 and dissolve it in 2 L of pure water. Add 25 wt% ammonia water to adjust the pH to 2.0. Add amino multi-walled carbon nanotubes and ultrasonically treat for 40 min. Let it stand for adsorption for 10 h. The amino content of the amino multi-walled carbon nanotubes is 0.45 wt%, and the specific surface area is 230 m 2 / g, and the mass ratio of amino-modified multi-walled carbon nanotubes to crude phosphoric acid was 3:1.

[0065] S2. After adsorption, the solid-liquid separation is carried out. The separated solution is treated with a sulfonic acid cationic resin (type 001×7) to remove metal ion impurities to obtain a purified solution. The exchange capacity of the sulfonic acid cationic resin is 4.5 mmol / g, the exchange resin height is 2 m, and the solution flow rate is 4 m / h.

[0066] The impurity element content in the purified solution was measured by inductively coupled plasma emission spectrometry. The results are shown in Table 10: Table 10

[0067] S3. The adsorbed amino multi-walled carbon nanotubes are desorbed using 15 wt% ammonia water to obtain an ammonium phosphate solution, which is slowly heated and decomposed at 200° C. for 40 min to obtain a high-purity phosphoric acid solution. The decomposed ammonia gas is absorbed by pure water to obtain ammonia water, which is recycled.

[0068] S4. Collect the high-purity phosphoric acid solution and the purified liquid, mix them to obtain a purified product, the mass of the purified product is m2 is 4028 g, and the phosphoric acid content W2 of the purified product is determined by weight method, W2 is 4.63%, and the impurity element content of the purified product is measured by inductively coupled plasma emission spectrometry. The impurity element content results are shown in Table 11: Table 11

[0069] The phosphoric acid recovery rate was calculated according to the formula: , Wherein, m2 is the mass of the purified product, g; m1 is the mass of the crude phosphoric acid used for purification, g; W1 is the phosphoric acid content of the crude phosphoric acid sample, %; and W2 is the phosphoric acid content of the purified product, %.

[0070] Substitute the above data into the formula for calculation. The specific calculation process is as follows: , The calculation results show that the phosphoric acid recovery rate P is 88.8%.

[0071] Example 5 The only difference from Example 1 is that ammonia water is added to S1 to adjust the pH to 4.0.

[0072] S1. Take 1 kg of crude phosphoric acid same as that in Example 1 and dissolve it in 2 L of pure water. Add 25 wt% ammonia water to adjust the pH to 4.0. Add amino multi-walled carbon nanotubes and ultrasonically treat for 40 min. Let it stand for adsorption for 10 h. The amino content of the amino multi-walled carbon nanotubes is 0.45 wt% and the specific surface area is 230 m 2 / g, and the mass ratio of amino-modified multi-walled carbon nanotubes to crude phosphoric acid was 3:1.

[0073] S2. After adsorption, the solid-liquid separation is carried out. The separated solution is treated with a sulfonic acid cationic resin (type 001×7) to remove metal ion impurities to obtain a purified solution. The exchange capacity of the sulfonic acid cationic resin is 4.5 mmol / g, the exchange resin height is 2 m, and the solution flow rate is 4 m / h.

[0074] The impurity element content in the purified solution was measured by inductively coupled plasma emission spectrometry. The results are shown in Table 12: Table 12

[0075] S3. The adsorbed amino multi-walled carbon nanotubes are desorbed using 15 wt% ammonia water to obtain an ammonium phosphate solution, which is slowly heated and decomposed at 200° C. for 40 min to obtain a high-purity phosphoric acid solution. The decomposed ammonia gas is absorbed by pure water to obtain ammonia water, which is recycled.

[0076] S4. Collect the high-purity phosphoric acid solution and the purified liquid, mix them to obtain a purified product, the mass of the purified product is m2 is 5036 g, and the phosphoric acid content W2 of the purified product is determined by weight method, W2 is 3.81%, and the impurity element content of the purified product is measured by inductively coupled plasma emission spectrometry. The impurity element content results are shown in Table 13: Table 13

[0077] The phosphoric acid recovery rate was calculated according to the formula: , Wherein, m2 is the mass of the purified product, g; m1 is the mass of the crude phosphoric acid used for purification, g; W1 is the phosphoric acid content of the crude phosphoric acid sample, %; and W2 is the phosphoric acid content of the purified product, %.

[0078] Substitute the above data into the formula for calculation. The specific calculation process is as follows: , The calculation results show that the phosphoric acid recovery rate P is 90.1%.

[0079] Example 6 The only difference from Example 1 is that the mass ratio of the amino-modified multi-walled carbon nanotubes to the crude phosphoric acid is 4:1.

[0080] S1. Take 1 kg of crude phosphoric acid from Example 1 and dissolve it in 2 L of pure water. Add 25 wt% ammonia water to adjust the pH to 3.0. Add amino-treated multi-walled carbon nanotubes and ultrasonically treat for 40 min. Let it stand for adsorption for 10 h. The amino content of the amino-treated multi-walled carbon nanotubes is 0.45 wt%, and the specific surface area is 230 m 2 / g, and the mass ratio of amino-modified multi-walled carbon nanotubes to crude phosphoric acid was 4:1.

[0081] S2. After adsorption, the solid-liquid separation is carried out. The separated solution is treated with a sulfonic acid cationic resin (type 001×7) to remove metal ion impurities to obtain a purified solution. The exchange capacity of the sulfonic acid cationic resin is 4.5 mmol / g, the exchange resin height is 2 m, and the solution flow rate is 4 m / h.

[0082] The impurity element content in the purified solution was measured by inductively coupled plasma emission spectrometry. The results are shown in Table 14: Table 14

[0083] S3. The adsorbed amino multi-walled carbon nanotubes are desorbed using 15 wt% ammonia water to obtain an ammonium phosphate solution, which is slowly heated and decomposed at 200° C. for 40 min to obtain a high-purity phosphoric acid solution. The decomposed ammonia gas is absorbed by pure water to obtain ammonia water, which is recycled.

[0084] S4. Collect the high-purity phosphoric acid solution and the purified liquid, mix them to obtain a purified product, the mass of the purified product is m2 is 4821 g, and the phosphoric acid content W2 of the purified product is determined by weight method, W2 is 4.37%, and the impurity element content of the purified product is measured by inductively coupled plasma emission spectrometry. The impurity element content results are shown in Table 15: Table 15

[0085] The phosphoric acid recovery rate was calculated according to the formula: , Wherein, m2 is the mass of the purified product, g; m1 is the mass of the crude phosphoric acid used for purification, g; W1 is the phosphoric acid content of the crude phosphoric acid sample, %; and W2 is the phosphoric acid content of the purified product, %.

[0086] Substitute the above data into the formula for calculation. The specific calculation process is as follows: , The calculation results show that the phosphoric acid recovery rate P is 98.2%.

[0087] Example 7 The only difference from Example 1 is that the mass ratio of the amino-modified multi-walled carbon nanotubes to the crude phosphoric acid is 5:1.

[0088] S1. Take 1 kg of crude phosphoric acid from Example 1 and dissolve it in 2 L of pure water. Add 25 wt% ammonia water to adjust the pH to 3.0. Add amino-treated multi-walled carbon nanotubes and ultrasonically treat for 40 min. Let it stand for adsorption for 10 h. The amino content of the amino-treated multi-walled carbon nanotubes is 0.45 wt%, and the specific surface area is 230 m 2 / g, and the mass ratio of amino-modified multi-walled carbon nanotubes to crude phosphoric acid was 5:1.

[0089] S2. After adsorption, the solid-liquid separation is carried out. The separated solution is treated with a sulfonic acid cationic resin (type 001×7) to remove metal ion impurities to obtain a purified solution. The exchange capacity of the sulfonic acid cationic resin is 4.5 mmol / g, the exchange resin height is 2 m, and the solution flow rate is 4 m / h.

[0090] The impurity element content in the purified solution was measured by inductively coupled plasma emission spectrometry. The results are shown in Table 16: Table 16

[0091] S3. The adsorbed amino multi-walled carbon nanotubes are desorbed using 15 wt% ammonia water to obtain an ammonium phosphate solution, which is slowly heated and decomposed at 200° C. for 40 min to obtain a high-purity phosphoric acid solution. The decomposed ammonia gas is absorbed by pure water to obtain ammonia water, which is recycled.

[0092] S4. The high-purity phosphoric acid solution and the purified liquid were collected and mixed to obtain a purified product. The mass of the purified product was m2, which was 4952 g. The phosphoric acid content W2 of the purified product was determined by gravimetric method. W2 was 3.81%. The impurity element content of the purified product was measured by inductively coupled plasma emission spectrometry. The impurity element content results are shown in Table 17: Table 17

[0093] The phosphoric acid recovery rate was calculated according to the formula: , Wherein, m2 is the mass of the purified product, g; m1 is the mass of the crude phosphoric acid used for purification, g; W1 is the phosphoric acid content of the crude phosphoric acid sample, %; and W2 is the phosphoric acid content of the purified product, %.

[0094] Substitute the above data into the formula for calculation. The specific calculation process is as follows: , The calculation results show that the phosphoric acid recovery rate P is 98.3%.

[0095] Example 8 The only difference from Example 1 is that in S3, the concentration of the ammonia water is 10 wt %.

[0096] S1. Take 1 kg of crude phosphoric acid from Example 1 and dissolve it in 2 L of pure water. Add 25 wt% ammonia water to adjust the pH to 3.0. Add amino-treated multi-walled carbon nanotubes and ultrasonically treat for 40 min. Let it stand for adsorption for 10 h. The amino content of the amino-treated multi-walled carbon nanotubes is 0.45 wt%, and the specific surface area is 230 m 2 / g, and the mass ratio of amino-modified multi-walled carbon nanotubes to crude phosphoric acid was 3:1.

[0097] S2. After adsorption, the solid-liquid separation is carried out. The separated solution is treated with a sulfonic acid cationic resin (type 001×7) to remove metal ion impurities to obtain a purified solution. The exchange capacity of the sulfonic acid cationic resin is 4.5 mmol / g, the exchange resin height is 2 m, and the solution flow rate is 4 m / h.

[0098] The impurity element content in the purified solution was measured by inductively coupled plasma emission spectrometry. The results are shown in Table 18: Table 18

[0099] S3. The adsorbed amino multi-walled carbon nanotubes are desorbed using 10 wt% ammonia water to obtain an ammonium phosphate solution, which is slowly heated and decomposed at 200° C. for 40 min to obtain a high-purity phosphoric acid solution. The decomposed ammonia gas is absorbed by pure water to obtain ammonia water, which is recycled.

[0100] S4. The high-purity phosphoric acid solution and the purified liquid were collected and mixed to obtain a purified product. The mass of the purified product was m2, which was 5581 g. The phosphoric acid content W2 of the purified product was determined by gravimetric method. W2 was 3.60%. The impurity element content of the purified product was measured by inductively coupled plasma emission spectrometry. The impurity element content results are shown in Table 19. Table 19

[0101] The phosphoric acid recovery rate was calculated according to the formula: , Wherein, m2 is the mass of the purified product, g; m1 is the mass of the crude phosphoric acid used for purification, g; W1 is the phosphoric acid content of the crude phosphoric acid sample, %; and W2 is the phosphoric acid content of the purified product, %.

[0102] Substitute the above data into the formula for calculation. The specific calculation process is as follows: , The calculation results show that the phosphoric acid recovery rate P is 94.3%.

[0103] Example 9 The only difference from Example 1 is that in S3, the concentration of the ammonia water is 28 wt %.

[0104] S1. Take 1 kg of crude phosphoric acid from Example 1 and dissolve it in 2 L of pure water. Add 25 wt% ammonia water to adjust the pH to 3.0. Add amino-treated multi-walled carbon nanotubes and ultrasonically treat for 40 min. Let it stand for adsorption for 10 h. The amino content of the amino-treated multi-walled carbon nanotubes is 0.45 wt%, and the specific surface area is 230 m 2 / g, and the mass ratio of amino-modified multi-walled carbon nanotubes to crude phosphoric acid was 3:1.

[0105] S2. After adsorption, the solid-liquid separation is carried out. The separated solution is treated with a sulfonic acid cationic resin (type 001×7) to remove metal ion impurities to obtain a purified solution. The exchange capacity of the sulfonic acid cationic resin is 4.5 mmol / g, the exchange resin height is 2 m, and the solution flow rate is 4 m / h.

[0106] The impurity element content in the purified solution was measured by inductively coupled plasma emission spectrometry. The results are shown in Table 20: Table 20

[0107] S3. The adsorbed amino multi-walled carbon nanotubes are desorbed using 28 wt% ammonia water to obtain an ammonium phosphate solution, which is slowly heated and decomposed at 200° C. for 40 min to obtain a high-purity phosphoric acid solution. The decomposed ammonia gas is absorbed by pure water to obtain ammonia water, which is recycled.

[0108] S4. The high-purity phosphoric acid solution and the purified liquid were collected and mixed to obtain a purified product. The mass of the purified product was m2, which was 3897 g. The phosphoric acid content W2 of the purified product was determined by gravimetric method. W2 was 3.60%. The impurity element content of the purified product was measured by inductively coupled plasma emission spectrometry. The impurity element content results are shown in Table 21: Table 21

[0109] The phosphoric acid recovery rate was calculated according to the formula: , Wherein, m2 is the mass of the purified product, g; m1 is the mass of the crude phosphoric acid used for purification, g; W1 is the phosphoric acid content of the crude phosphoric acid sample, %; and W2 is the phosphoric acid content of the purified product, %.

[0110] Substitute the above data into the formula for calculation. The specific calculation process is as follows: , The calculation results show that the phosphoric acid recovery rate P is 94.6%.

[0111] Comparative Example 1 The only difference from Example 1 is that the precipitation method is used to remove metal ion impurities in this comparative example.

[0112] Take 1 kg of the same crude phosphoric acid as in Example 1 and dissolve it in 2 L of pure water. Add 25 wt% ammonia water dropwise while stirring to adjust the pH to 8.5. After the addition is completed, filter to obtain a filtrate, and weigh the filtrate to obtain 3161 g.

[0113] The impurity element content in the filtrate was measured by inductively coupled plasma optical emission spectrometry. The results are shown in Table 22: Table 22

[0114] The phosphoric acid content W2 of the filtrate was determined by weight method and was 4.64%.

[0115] The phosphoric acid recovery rate was calculated according to the formula: , Wherein, m2 is the mass of the filtrate, g; m1 is the mass of the crude phosphoric acid used for purification, g; W1 is the phosphoric acid content of the crude phosphoric acid sample, %; and W2 is the phosphoric acid content of the filtrate, %.

[0116] Substitute the above data into the formula for calculation. The specific calculation process is as follows: , The calculation results show that the phosphoric acid recovery rate P is 68.9%.

[0117] Comparative Example 2 The only difference from Example 1 is that in this comparative example, metal ion impurities are removed by cation exchange resin.

[0118] S1. Take 1 kg of the crude phosphoric acid obtained in Example 1, dissolve it in 2 L of pure water, and add 25 wt% ammonia water to adjust the pH to 3.0.

[0119] S2. The solution is treated with a sulfonic acid cationic resin (type 001×7) to remove metal ion impurities to obtain a purified liquid. The mass of the purified liquid is 2856 g, wherein the exchange capacity of the sulfonic acid cationic resin is 4.5 mmol / g, the exchange resin height is 2 m, and the solution flow rate is 4 m / h.

[0120] The impurity element content in the purified solution was measured by inductively coupled plasma emission spectrometry. The results are shown in Table 23: Table 23

[0121] The phosphoric acid content W2 of the purified solution was determined by weight method, and W2 was 5.66%.

[0122] The phosphoric acid recovery rate was calculated according to the formula: , Wherein, m2 is the mass of the purified liquid, g; m1 is the mass of the crude phosphoric acid used for purification, g; W1 is the phosphoric acid content of the crude phosphoric acid sample, %; and W2 is the phosphoric acid content of the purified liquid, %.

[0123] Substitute the above data into the formula for calculation. The specific calculation process is as follows: , The calculation results show that the phosphoric acid recovery rate P is 75.9%.

[0124] Comparative Example 3 The only difference from Example 1 is that in this comparative example, the metal ion impurities are removed directly by the cation exchange resin without adjusting the pH.

[0125] S1. Take 1 kg of the same crude phosphoric acid as in Example 1 and dissolve it in 2 L of pure water.

[0126] S2. The solution is treated with a sulfonic acid cationic resin (type 001×7) to remove metal ion impurities to obtain a purified liquid. The mass of the purified liquid is 2810 g, wherein the exchange capacity of the sulfonic acid cationic resin is 4.5 mmol / g, the exchange resin height is 2 m, and the solution flow rate is 4 m / h.

[0127] The impurity element content in the purified solution was measured by inductively coupled plasma emission spectrometry. The results are shown in Table 24: Table 24

[0128] The phosphoric acid content W2 of the purified liquid was determined by weight method, and W2 was 5.94%.

[0129] The phosphoric acid recovery rate was calculated according to the formula: , Wherein, m2 is the mass of the purified liquid, g; m1 is the mass of the crude phosphoric acid used for purification, g; W1 is the phosphoric acid content of the crude phosphoric acid sample, %; and W2 is the phosphoric acid content of the purified liquid, %.

[0130] Substitute the above data into the formula for calculation. The specific calculation process is as follows: , The calculation results show that the phosphoric acid recovery rate P is 78.4%.

[0131] The phosphoric acid recovery rates of the above examples and comparative examples are shown in Table 25: Table 25

[0132] In the above examples, crude phosphoric acid with different phosphoric acid contents in Examples 1 to 3 is purified by the purification method of the present invention, and the impurity element content in the purified product is low and the phosphoric acid recovery rate is high. Based on the influence of the purification treatment under different pH, when the pH is 2.0 or 4.0 in Example 4 and Example 5, the adsorption effect of the amino multi-walled carbon nanotubes is reduced, and there is surface phosphate precipitation and blockage during subsequent cationic resin treatment, which reduces the removal effect of metal ion impurities and the recovery rate of phosphoric acid. Example 6 and Example 7 increase the amount of adsorbent amino multi-walled carbon nanotubes, and Example 7 reflects that the effect of excessive addition on the recovery rate of phosphoric acid is reduced. The desorption rate of amino multi-walled carbon nanotubes directly affects the recovery rate of phosphoric acid. When desorbed using ammonia water of different concentrations, the concentration of Example 1 is more suitable. In combination with the comparative examples and examples, it can be seen that the purification method of the present invention can not only ensure the purification effect, but also maximize the reduction of the loss of phosphoric acid in the purification, thereby improving the product value.

[0133] It should be noted that, in this document, relational terms such as first and second, etc., are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the terms "comprises," "comprising," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a list of elements includes not only those elements but also other elements not explicitly listed, or elements inherent to such process, method, article, or apparatus.

[0134] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.

Claims

1. A method for purifying phosphoric acid, characterized in that: The following steps are involved: S1. Dissolve the crude phosphoric acid in water, adjust the pH to 2-4 with aqueous ammonia, add amino-modified multi-walled carbon nanotubes, ultrasonicate for 30-50 min, and allow to stand for adsorption for 8-12 h; S2, solid-liquid separation after adsorption, the separated solution is treated with sulfonic acid cationic resin to remove metal ion impurities to obtain a purified solution; S3, desorbing the adsorbed amino multi-walled carbon nanotubes with ammonia water to obtain an ammonium phosphate solution, which is heated and decomposed to obtain a high-purity phosphoric acid solution, and the decomposed ammonia is absorbed by pure water to obtain ammonia water, which is recycled; S4. Collect the high-purity phosphoric acid solution and the purified liquid to obtain a purified product.

2. A method for purifying phosphoric acid according to claim 1, characterized in that, The phosphoric acid content in the crude phosphoric acid product is ≥20 wt %.

3. A method for purifying phosphoric acid according to claim 1, characterized in that, In S1, the concentration of the ammonia water is 20-40 wt %.

4. A method for purifying phosphoric acid according to claim 1, characterized in that: The amino content of the aminated multi-walled carbon nanotubes is 0.4-0.6 wt % and the specific surface area is 200-260 m 2 / g.

5. A method for purifying phosphoric acid according to claim 1, characterized in that: The mass ratio of the amino-modified multi-walled carbon nanotubes to the crude phosphoric acid is 3-5:

1.

6. A method for purifying phosphoric acid according to claim 1, characterized in that: The exchange capacity of the sulfonic acid cationic resin is ≥4.0 mmol / g.

7. A method for purifying phosphoric acid according to claim 1, characterized in that: The purified liquid contains Al<50ppm, Ca<200ppm, and Mg<2000ppm.

8. A method for purifying phosphoric acid according to claim 1, characterized in that: In S3, the concentration of the ammonia water is 10-28 wt %.

9. A method for purifying phosphoric acid according to claim 1, characterized in that: The temperature of the thermal decomposition is 180-220°C.

10. An application of the phosphoric acid purification method according to any one of claims 1 to 9, characterized in that: The phosphoric acid purification method is used to purify phosphoric acid, a raw material for preparing lithium iron phosphate batteries in actual production.

Citation Information

Patent Citations

  • Method for preparing carbon nanometer pipe

    CN101177252A

  • High-permeability selective acid-resistant nanofiltration membrane material as well as preparation method and application thereof

    CN113332859A

  • Lithium iron phosphate wastewater treatment and resource recovery method

    CN115072921A

  • Process for the production of phosphoric acid

    GB1222195A

  • Ceramic / carbon nanotube composite and preparing method thereof

    KR1020110097559A